The Conceptual Design of Recycled Micro-Library in RW 9 Kelurahan Merjosari - Malang - Muhammad Nelza Mulki Iqbal; Daim Tri Wahyono; Bambang Joko Wiji Utomo (Green Visioneers, 2021)
The conceptual design of recycled micro library in RW 9 Kelurahan Merjosari is a part of ongoing partnership with the residents of RW 9 Kelurahan Merjosari. The existence of this library is expected to be a common space for residents, especially children, to interact and learn collectively. The design method used on this research is the design process method starting from the assimilation stage, general study, development, and communication. This micro library design applies a recycled design principle for the selection of its materials and main structure, and it is in line with sustainable landscape concept in macro context. Additionally, the design acts as public generator by providing participatory space for its users through the application of a green wall that can be assembled and developed as needed. The main green wall is made through a re-use of plastic bottle with green plants insertion. Light steel, hollow and recycled teak pallets are used for the main structure, panels, and furniture.